Immune mechanisms in liver diseases - Klenerman, Paul (Henry Stewart Talks, 2023)
Liver immunology and tolerance, Components of the liver immune system, Immune-mediated pathology: viral hepatitis, Hepatitis B virus: chronic infection and chronic disease, Other immune-mediated pathologies